Optimization modeling of mixed gas engine types with different maintenance spans and costs: Case study OF CCHP to evaluate optimal gas engine operations and combination of the types. (1st May 2021) - Yamano, Shuhei; Nakaya, Takashi; Ikegami, Takashi; Nakayama, Masayuki; Akisawa, Atsushi
Abstract: Combined cooling, heat and power supply systems (CCHP) are expected as a method of efficient use of energy, and gas engines are installed for power and heat supply for them in many cases of District heat and power supply (DHC). Conventionally, it presupposed that the same type of multiple gas engines is installed in a site, and considering the terms of maintenance is only calculate the cost by simple multiplication with assumed unit price. There are two types for gas engines for CCHP such as High-speed type and Medium-speed type depending on the rated rotation speed. The characteristics are different in terms of initial cost, efficiency, and maintenance, and it is possible to install them on one site. Therefore, the objectives of this research are to model the optimal operation of CCHP combining High-speed type and Medium-speed type with the detail maintenance process that several stages are determined by operation hours for each type and to verify the effectiveness of vicarious combinations of different type gas engines and their operation from the economical point of view considering actual maintenance schedule. It is necessary to consider not only the load balance of each equipment but also the elapsed time axis to optimize actual maintenance activities because the maintenance timing is determined by the accumulation of operation hours. In this study, developed the methodology to solve the optimum operation plan of CCHP and the optimum maintenance plan of the gas engines at the same time, and the examined case was a DHC with 3 units of 3800 kW gas engines for the operation of 1 year. The results indicate that the proposed methodology is useful since the annual operation cost is decreased compared with the conventional method. By the optimization considering detail maintenance, engines' operation hours are controlled to optimize the number of maintenance work even among the same types. A combination of the two types would be better than the system with one type. It implies that the proposed methodology is effective to derive the optimal configuration of CCHP. Highlights: A model that optimizes the CCHP operation and maintenance plan simultaneously was formulated. Medium-speed and High-speed types of gas engines were considered in the optimization. The difference in maintenance activities depending on the engine type was taken into account. The gas engine combinations with Medium-speed and High-speed types were evaluated. Mixed configuration of the different types is suggested to be more advantageous than those of multiple single types.